2017
DOI: 10.1007/s10029-017-1617-8
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use is not associated with groin hernia repair, a population-based study

Abstract: PurposeThe pathogenesis of groin hernia is not fully understood and some suggested risk factors are debatable. This population-based study evaluates the association between groin hernia repair and tobacco use.MethodAn observational study based on register linkage between the Swedish Hernia Register and the Västerbotten Intervention Program (VIP). All primary groin hernia repairs performed from 2001 to 2013 in the county of Västerbotten, Sweden, were included.ResultsVIP provided data on the use of tobacco in 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…Smoking has been long proposed as a risk factor for IHRs, however, recent evidence refutes this theory. 22 Recently, Kevric et al 8 reported that Australia had a small increase in the incidence of groin hernia repairs (i.e. inguinal and femoral) over a similar time period, opposite of the findings reported in this current study.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Smoking has been long proposed as a risk factor for IHRs, however, recent evidence refutes this theory. 22 Recently, Kevric et al 8 reported that Australia had a small increase in the incidence of groin hernia repairs (i.e. inguinal and femoral) over a similar time period, opposite of the findings reported in this current study.…”
Section: Discussioncontrasting
confidence: 84%
“…Another possible explanation for the decreasing IHR rates posed by the authors of the American study was the change in smoking patterns over time. Smoking has been long proposed as a risk factor for IHRs, however, recent evidence refutes this theory 22 …”
Section: Discussionmentioning
confidence: 99%
“…A low BMI, high age and previous hernia repair was found to be associated with an increased risk of inguinal hernia formation as have others [18,19,27].…”
Section: Discussionmentioning
confidence: 81%
“…Based upon previous studies possibly important variables for developing inguinal hernia such as age, previous inguinal hernia repair, comorbidity in terms of pulmonary disease, diabetes, degree of physical workload, high and low BMI, smoking, level of physical activity, pelvic lymph node dissection and clinical tumor stage [17][18][19][20], were retrieved from baseline questionnaire and clinical record forms.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Patients with IH had a slightly lower imputed BMI and were more likely to have used tobacco compared with control individuals, consistent with prior reports. 16,26 Both patients with IH and control individuals had a mean of more than 6 years of follow-up in Utah dur- ing a 20-year study period (1996-2015) based on UPDB demographic and medical records ( Table 2).…”
Section: Participant Characteristicsmentioning
confidence: 99%